Performance analysis of integrated solar heat pump VRF system for the low energy building in Mediterranean island. (August 2021) - Gilani, Hooman Azad; Hoseinzadeh, Siamak; Karimi, Hirou; Karimi, Ako; Hassanzadeh, Amir; Garcia, Davide Astiaso
Abstract: Cyprus is a heavily energy-receiving country, importing over 90% of its energy demand. Since heating and cooling of buildings account for roughly half of the yearly global energy consumptions, energy efficiency in cooling/heating systems, and devising renewable energy AC systems could contribute to significant alleviation in the energy situation of Cyprus. High levels of solar radiation are available in Cyprus and any attempt to devise or implement a solar AC system with feasible costs could be worthwhile. In this paper, energy performance and power generation of a variable refrigerant flow (VRF) heat pump system integrated with PV technology in a 5-story residential building in Cyprus are investigated. The yearly horizontal radiation intensity in the selected locations ranges from 1, 784 to 1, 882 kWh/m 2 . Yearly VRF power consumption ranges from 14, 005 to 18, 710 kWh and a PV array with a total capacity of 13 kW can generate between 23, 200 and 23, 650 kWh annually. PV arrays satisfy 126–166% of the annual VRF energy demand. Moreover, the installation of the PV system reduces approximately 14 tons of CO2 each year. Finally, an economic feasibility study indicates that the installation of PV arrays for this application in all investigated locations is financially profitable and for a 20-year investment period, the net present value of the project would vary from 4, 843 to 13, 355 . Highlights: Energy performance and power generation of VRF-PV technology residential building in Cyprus is investigated. The yearly horizontal radiation intensity in the selected locations ranges from 1, 784 to 1, 882 kWh/m 2 . PV arrays satisfy 126–166% of the annual VRF energy demand. The installation of the PV system reduces approximately 14 tons of CO2 each year. The value of the project would vary from 83, 947 to 88, 647 for 20-year investment period.